Influence of soil texture, climate and vegetation cover on secondary soil salinization in Pampas plains, South America - Milione, Germán Marcelo (2020)
Land-use change from herbaceous to woody cover -or vice versa- largely affects water fluxes, which in turn can mobilize existing salts dissolved in the soil, and thereby negatively affect soil and/or water quality and site productivity. Secondary salinization was observed after afforestation at the Northern and Eastern subregions of the Río de la Plata Grassland. Based on this, our objective was to determine the degree of association between the climatic (e.g. water balance), edaphic (e.g. texture, presence of petrocalcic horizons) and biological factors (age of plantation, stand density and stand basal area) with the secondary salinization processes under the particular environmental conditions of the Austral Pampas. The lowest electrical conductivity (EC, µS.cm-1) values were found in sites with sandy-textured soils and negative water balance, regardless of tree canopy cover. When EC differences did occur between land uses of the same site (50% of the sites), in most cases - but not in all of them - the highest EC was measured under tree cover. When salinization was significant, no pattern was observed in the salt distribution along the soil profile. An increase of EC was associated with the oldest-unmanaged plantations, with mean age of 40 years, a period much longer than the productive rotation recommended. Under similar edaphic conditions where salinization was observed (i.e. clayed soils, with naturally high salt level), salinization was not significant in relatively young plantations (